THE EFFECT OF GIVE THE MONEY LEARNING MODEL COMBINED WITH DIGITAL ANIMATION MEDIA ON STUDENTS' SOCIAL STUDIES LEARNING ACHIEVEMENTS AT SMPN 1 SEUNAGAN (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
ABSTRACT This study is entitled the influence of the use of active learning models with the strategy Give the Money on the social studies learning achievement of SMPN 1 Seunagan students. The purpose of this study is to determine the influence of the use of active learning models with the strategy Give the Money on the social studies learning achievement of SMPN 1 Seunagan students. This study uses a quantitative approach and experimental research type. The population in this study were all grade VII students and the sample consisted of 42 students in the experimental and control classes. The data collection technique in the study was carried out by giving a test. Based on the results of the study, it is known that (1) in terms of homogeneity, the two classes used as samples are homogeneous. This result can be seen from the results of the hypothesis test with the calculation results of F count = 1.01 and F table = 2.12, so the data for both classes is homogeneous or comes from the same population, (2) for the normality test of the experimental class, X2 count = 1.05 and X2 table = 5.99 were obtained and the normality test of the control class was X2 count = 0.09 and x2 table = 5.99, so it can be said that the control class data is normally distributed, (3) the results of the hypothesis test using the t-test and obtained t count = 2.70 and the t table value at the significance level α = 0.05 (one-sided test) with dk = 40 is 1.68 accept Ha if t count > t table, where t count = 2.70 and t table = 1.68 or 2.70 > 1.68 then Ha is accepted. The research hypothesis stating that the learning outcomes of students taught using the active learning model with the Give the Money strategy are better than the learning outcomes of students taught using the conventional learning model can be accepted as true or in other words the research hypothesis is accepted. Keywords: Active Learning, Give the Money Model, Digital Animation Media, Learning Achievement.